Laboratory information system requirements to manage the COVID-19 pandemic: A report from the Belgian national reference testing center. (18th June 2020) - Weemaes, Matthias; Martens, Steven; Cuypers, Lize; Van Elslande, Jan; Hoet, Katrien; Welkenhuysen, Joris; Goossens, Ria; Wouters, Stijn; Houben, Els; Jeuris, Kirsten; Laenen, Lies; Bruyninckx, Katrien; et al.
Abstract: Objective: The study sought to describe the development, implementation, and requirements of laboratory information system (LIS) functionality to manage test ordering, registration, sample flow, and result reporting during the coronavirus disease 2019 (COVID-19) pandemic. Materials and Methods: Our large (>12 000 000 tests/y) academic hospital laboratory is the Belgian National Reference Center for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing. We have performed a moving total of >25 000 SARS-CoV-2 polymerase chain reaction tests in parallel to standard routine testing since the start of the outbreak. A LIS implementation team dedicated to develop tools to remove the bottlenecks, primarily situated in the pre- and postanalytical phases, was established early in the crisis. Results: We outline the design, implementation, and requirements of LIS functionality related to managing increased test demand during the COVID-19 crisis, including tools for test ordering, standardized order sets integrated into a computerized provider order entry module, notifications on shipping requirements, automated triaging based on digital metadata forms, and the establishment of databases with contact details of other laboratories and primary care physicians to enable automated reporting. We also describe our approach to data mining and reporting of actionable daily summary statistics to governing bodies and other policymakers. Conclusions: Rapidly developed, agile extendable LIS functionality and its meaningful use alleviates the administrative burden on laboratory personnel and improves turnaround time of SARS-CoV-2 testing. It will be important to maintain an environment that is conducive for the rapid adoption of meaningful LIS tools after the COVID-19 crisis.